2013
DOI: 10.3390/molecules18077584
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic-Like and Antinociceptive Effects of 2(S)-Neoponcirin in Mice

Abstract: Study aims: 2(S)-neopincirin (NEO) is a constituent from of Clinopodium mexicanum, which is used in traditional Mexican herbal medicine for its tranquilizing and analgesic properties. This study investigated the anxiolytic-like, sedative and antinociceptive effects of NEO in several mice models. Material and methods: The anxiolytic-like effect was evaluated in the hole-board (HBT) and Open Field Tests (OFT); sedative effect was evaluated in sleeping time induced by sodium pentobarbital, and its antinociceptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Ponciri Fructus is a widely used a traditional herbal medicine. It has been reported that three flavonoids (naringin, neoponcirin and poncirin) and three coumarins (umbelliferone, imperatorin and auraptene) isolated from the 70% ethanolic extract of Ponciri fructus have various pharmacological actions including antioxidant [ 27 ], anxiolytic-like [ 28 ], anticancer [ 29 ], and anti-inflammatory effects [ 30 32 ]. Therefore, we propose that PFE can have antiproliferative and antioxidant effects based on the various pharmacological activities of the chemical-chemical interactions on the development and progression of lesions in a TP-induced model of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Ponciri Fructus is a widely used a traditional herbal medicine. It has been reported that three flavonoids (naringin, neoponcirin and poncirin) and three coumarins (umbelliferone, imperatorin and auraptene) isolated from the 70% ethanolic extract of Ponciri fructus have various pharmacological actions including antioxidant [ 27 ], anxiolytic-like [ 28 ], anticancer [ 29 ], and anti-inflammatory effects [ 30 32 ]. Therefore, we propose that PFE can have antiproliferative and antioxidant effects based on the various pharmacological activities of the chemical-chemical interactions on the development and progression of lesions in a TP-induced model of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that three flavonoids (naringin, neoponcirin and poncirin) and three coumarins (umbelliferone, imperatorin and auraptene) isolated from the 70% ethanolic extract of Ponciri fructus have various pharmacological actions including antioxidant [27], anxiolytic-like [28], anticancer [29], and anti-inflammatory effects [30][31][32]. Therefore, we propose that PFE can have antiproliferative and antioxidant effects based on the various pharmacological activities of the chemical-chemical interactions on the development and progression of lesions in a TP-induced model of BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, didymin is the leading constituent of the complex mixture of flavonoids present in the active extracts of Clinopodium mexicanum . Therefore, in their follow-up study, Cassani et al evaluated the in vivo sedative, anxiolytic-like and antinociceptive effects of didymin which was isolated from leaves of Clinopodium mexicanum [ 41 ]. Didymin showed significant anxiolytic-like activities and was able to against thermal stimuli-induced nociception, and this anxiolytic-like action could be blocked by pitrotoxin but was enhanced by muscimol.…”
Section: Therapeutic Bioactivities: Protective Effects and Health mentioning
confidence: 99%